Technological quality of spent hen Pectoratis major as influenced by ultrasonication - Faurillo, Charity G.
Efficient utilization of meat from spent hens has been a major issue for the egg industry. The toughness of spent hen meat is undesirable for processors and consumers, making it a low-value and underutilized protein source. Ultrasound is a rapid, economical, and energy-efficient technology that has been used to tenderize beef, pork, and poultry meat. In this study, the effect of different combinations of ultrasonication temperature (5, 15, and 25°C) and duration (0, 10, 20, and 30 min) on the technological properties (CIE L*a*b*, pH, water-holding capacity, Warner-Bratzler shear force, and microstructure) of spent hen Pectoralis major was investigated. L* values and pH values were not significantly affected by sonication but remained within the ‘normal’ range for chicken meat lightness. On the other hand, a* and b* values, and water-holding capacity significantly (p<0.05) changed due to ultrasound parameters. Additionally, a significant relationship between WHC and WBSF was detected (r=-0.443; p<0.01). WBSF values had no significant changes after sonication but the overall means indicated a trend. Signal-to-noise ratios of WBSF means suggested 10 min and 5°C as the optimal levels for treatment duration and temperature, respectively. Using the optimal settings, the effect of ultrasound on the microstructure of spent hen meat was evaluated. Qualitative analysis of scanning electron microscopy (SEM) images revealed that sonication led to fragmented muscle fibers, deformed and separated fiber bundles, and disrupted connective tissues. While ultrasound was unable to significantly affect the toughness of spent hen meat, microstructural analysis indicated evidence of the tenderizing effects of ultrasound.